2014
DOI: 10.1177/0363546514539449
|View full text |Cite
|
Sign up to set email alerts
|

On-Field Performance of National Football League Players After Return From Concussion

Abstract: No difference in player performance after concussion was found whether the player did or did not miss games before return. Return without missing games may be associated with experience and timing of injury within a season and less likely after newer guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 34 publications
8
55
2
Order By: Relevance
“…Interestingly, studies investigating postconcussion performance of elite Australian Football players [33] and National Football League (NFL) players [32] have both reported results similar to the current study, in that principally no difference from baseline performance existed, speaking to the transient nature of SRC. These previous studies have also suggested that null findings in pre-to post-injury performances likely indicate appropriate medical management [32,33], or the ability of elite athletes to compensate and optimize immediate performance.…”
Section: Postconcussion Performance Across Professional Sportssupporting
confidence: 77%
See 3 more Smart Citations
“…Interestingly, studies investigating postconcussion performance of elite Australian Football players [33] and National Football League (NFL) players [32] have both reported results similar to the current study, in that principally no difference from baseline performance existed, speaking to the transient nature of SRC. These previous studies have also suggested that null findings in pre-to post-injury performances likely indicate appropriate medical management [32,33], or the ability of elite athletes to compensate and optimize immediate performance.…”
Section: Postconcussion Performance Across Professional Sportssupporting
confidence: 77%
“…Prior to this study, only three studies have addressed postconcussion performance in elite athletes [21,32,33]. The present study extends the study of postconcussion performance to elite basketball players.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Return-to-play decisions are currently based on clinical judgment that is informed by neurocognitive batteries and selfreport symptom metrics rather than on evidence-based biomarkers. 10,22,39,62 Our study suggests a potential objective marker of physiological recovery indicating that the WoCV has elapsed and the individual is safe to resume activity. 10 Yet to be fully elucidated, there are several possible pathophysiologic mechanisms of decreased CBF after mTBI.…”
Section: Discussionmentioning
confidence: 80%